Makassar Goes Global: Pengaruh UNWTO dalam Transformasi Makassar sebagai Destinasi MICE - Suci Anggraheni Bagenda; Atika Puspita Marzaman (Lembaga Pengembangan Kinerja Dosen, 2024)
This research delves into the development of the tourism sector in Makassar through the lens of the concept and the role of the United Nations World Tourism Organization (UNWTO) in the Meetings, Incentives, Conventions, and Exhibitions (MICE) in Makassar. Employing a qualitative method and document analysis, the study explores the implementation of sustainable tourism principles amidst technological evolution. UNWTO is identified as a key catalyst in driving the adoption of cutting-edge technology in the tourism sector, enhancing tourism security, and improving industry skills. The research findings indicate that collaboration with UNWTO can have a positive impact on advancing tourism in Makassar, particularly in introducing innovative technologies and enhancing service quality. This study provides a profound understanding for stakeholders regarding sustainable tourism development strategies, positioning Makassar as a prominent destination. The implications of these research findings stimulate further considerations, including strengthening collaboration with UNWTO, continuously improving tourism infrastructure, and intensifying industry training to ensure the sustainability and competitiveness of this destination on the global stage.